Нетрадиционные и возобновляемые источники энергии: учебное пособие - Губин В. Е. Владимир Евгеньевич; Матвеева А. А. Анастасия Александровна; Гвоздяков Д. В. Дмитрий Васильевич; Янковский С. А. Станислав Александрович; Ларионов К. Б. Кирилл Борисович; Слюсарский К. В. Константин Витальевич; Марышева Я. В. Яна Владимировна; Цибульский С. А. Святослав Анатольевич; Зенков А. В. Андрей Викторович; Лавриненко С. В. Сергей Викторович (Томск, Изд-во ТПУ, 2019)
Заглавие с титульного экрана